IMPLEMENTASI KURIKULUM 2013 MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMP NEGERI 6 AMBARAWA SATU ATAP - Mika Husyada (Al Ghazali, 2019)
This study aims to find out how (1) implementation of curriculum 2013 in SMP Negeri 6 AmbarawaSatuAtap subject of Islamic Religious Education (2) Factors that hamper and support (3) effort done by school in overcoming obstacle of 2013 at SMP Negeri 6 AmbarawaSatuAtap. The results showed that the curriculum of 2013 in SMP Negeri 6 AmbarawaSatuAtap still not maximal because it still use KTSP learning device. The learning process is mainly on the subjects of Islamic religious education coverage of the material that is too broad so that the lack of face-to-face time, the lack of availability of facilities prasana, and educators who are still less than the maximum in teaching. The curriculum in 2013 focuses more on student activeness and requires students to seek other knowledge from various sources. From the results of interviews conducted, it was concluded that the teachers felt that they have not been able to make the learning tools of the 2013 curriculum and the students have little difficulty in finding the wider material because of the limited facilities. Education infrastructure is one of the important resources in the utilization and management, so that the expected goals can be achieved.